Racial Disparities in Time to Treatment Initiation and Outcomes for Early Stage Anal Squamous Cell Carcinoma. (November 2020) - Goksu, Suleyman Y.; Ozer, Muhammet; Kazmi, Syed M.A.; Aguilera, Todd A.; Ahn, Chul; Hsiehchen, David; Sanjeevaiah, Aravind; Maxwell, Mary C.; Beg, Muhammad S.; Sanford, Nina N.
Abstract : Objectives: Although cure rates for early stage anal squamous cell cancer (ASCC) are overall high, there may be racial disparities in receipt of treatment and outcome precluding favorable outcomes across all patient demographics. Therefore, the authors aimed to assess the time to treatment initiation and overall survival (OS) in Black and White patients receiving definitive chemoradiation for early stage ASCC. Materials and Methods: The authors identified patients diagnosed with early stage (stage I-II) ASCC and treated with chemoradiation diagnosed between 2004 and 2016 in the National Cancer Database. Clinical and treatment variables were compared by race using the χ 2 test, and OS assessed through Cox regression with 1:1 nearest neighbor propensity score matching. Results: Among 9331 patients, 90.6% were White. Black patients had longer median time to treatment initiation as compared with White patients (47 vs. 36 d, P <0.001), and on multivariable analysis, the Black race was associated with higher odds of >6 weeks of time to treatment initiation (hazard ratio, 1.78; 95% confidence interval, 1.53-2.08; P <0.001). Furthermore, Black patients had worse OS (5-year survival 71% vs. 77%; P <0.001), which persisted after propensity score matching ( P= 0.007). Conclusions: Black patients had a longer time to treatment initiation and worse OS as compared with White patients with early stage ASCC treated with chemoradiation. Further research is needed to better elucidate the etiologies of these disparities.